2020
DOI: 10.3390/jcm9041238
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Measuring the Volumetric Change of Alveolar Bone Around Dental Implants Using Computed Tomography

Abstract: This study proposes a method for measuring the volumetric change of alveolar bone after dental implant surgery using computed tomography (CT). A total of 40 implants in 20 patients (15 males and 5 females) were selected. The types of implants used were group 1: 24 CMI IS-II Active implants (Neobiotech Co., Seoul, Republic of Korea) and group 2: 16 SLActive Bone Level implants (Institut Straumann AG, Basel, Switzerland). The OnDemand3D software (CyberMed, Seoul, Korea) was used for analysis. The volumetric chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In areas grafted with DBB, the micro-CT analysis did not obtain the same level of correlation observed in regions of NB in the volumetric analysis. Previous studies have reported the occurrence of artifacts around radiopaque bodies that interfere with interface analyzes (20), such as between bone and dental implant or between bone tissue and different types of biomaterials (21,22). Although other studies demonstrate results in which there is a separation between radiopaque bone substitutes and host bone tissue, it is likely that the differences between biomaterials, experimental models and evaluated periods justify the differences with the findings of this study (20).…”
Section: Discussionmentioning
confidence: 58%
“…In areas grafted with DBB, the micro-CT analysis did not obtain the same level of correlation observed in regions of NB in the volumetric analysis. Previous studies have reported the occurrence of artifacts around radiopaque bodies that interfere with interface analyzes (20), such as between bone and dental implant or between bone tissue and different types of biomaterials (21,22). Although other studies demonstrate results in which there is a separation between radiopaque bone substitutes and host bone tissue, it is likely that the differences between biomaterials, experimental models and evaluated periods justify the differences with the findings of this study (20).…”
Section: Discussionmentioning
confidence: 58%
“…Another drawback is the use of 2D radiographs only for linear measurements; thus, volumetric measurement of the crestal bone cannot be employed around dental implants. In the literature, marginal bone change around the apex of the dental implants can be observed [ 48 ]. The power of the study would be increased by larger sample sizes; thus, multiple centers, randomized, prospective clinical trials are necessary to validate the present outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The use of 2D radiographs was limited to the measurement of the mesiodistal MBL; thus, the buccolingual bone level and crestal bone volume around the dental implants could not be measured. In previous studies, the change in the buccolingual MBL and bone volume around implants could be examined using cone-beam computed tomography [ 34 , 35 ]. The crestal marginal bone resorption around dental implants is also associated with the surgical protocol used [ 36 ].…”
Section: Discussionmentioning
confidence: 99%